Largest testicular tumour in South-East Asia: a case report - Aizat, S. I.; Yusof, M. R.; Lee, F. Y.; Fahmy, O.; Lee, C. K.S.; Khairul Asri, M. G.; Muhammad Nasrulazam, N.; Vikinesan, V. K.; Liyana Zayani, Y.; Yusuf, M.; Rashide, Y.; Othman, A. (Publishing House ABV Press, 2023)
We present the largest testicular tumour that first ever reported in Malaysia and we believed first reported in Southeast Asia. A 21 years old Malay gentleman presented to us with painless large scrotal swelling. After the initial workup and investigations were done and followed by a CT scan which yield a multiple paraaortic lymph nodes, the patient was scheduled listed in the earliest list for high ligation right orchidectomy with an inguinal approach. The patient seeks treatment at that point because he can't bear the embarrassment and fear of the treatment.